Tsunami hazard mitigation by mangrove forests-experiment on hydrodynamic coefficients - Sim, Shawn Yi Sheng. (2010)
This report is an overview of my final year project (FYP) done in Nanyang Technological University (NTU). The main scope of this project is to understand the importance of mangrove forests in mitigating tsunamis. Through recent global incidents, we have come to realize the devastating effects of tsunamis. It is then important to find a way to lessen its impacts. One suggested way is to use the mangrove forests. Thus, this project will analyse the effectiveness of mangrove forests in mitigating this natural disaster. We will be focusing on this scope by paying great attention to the changes in drag coefficient due to changes in the compactness or sparseness of a mangrove forest. The contents of this report will then include a brief review on the background of tsunamis and the mangrove forests as well as steps to conduct the experiment. Finally, I will end off with a section discussing the results obtained and evaluating the numerically simulated data obtained.